Multiplikasi Mata Tunas Pisang ‘Cavendish’ In Vitro Pada Berbagai Konsentrasi Benziladenin - Maulida, Desi; Erfa, Lisa; Sesanti, Rizka Novi (Jurnal Penelitian Pertanian Terapan, 2018)
Banana is one of the most important global agriculture commodities. Asia accounts for the production of bananas amounted to 56.4% of total banana in the world and Indonesia is one of the banana-producing countries in Asia. The demand for bananas increased need is anticipated with good cultivation techniques to meet domestic and international market demand. Plant regeneration in vitro tissue culture techniques or can be used to produce propagules true-to-type in large quantities in a relatively short period and free from disease. This research aims to study the influence of various concentrations of BA (0, 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, and 4.0 mg/l) against the growth and reproduction of Cavendish banana propagules in vitro. Time appears buds, propagules length and the number of propagules per explant, and the number of primary roots of plants per explant observed after eight weeks of culture. The experiment results show that after explant grown for eight weeks on the media's treatment shows the different response. The increased concentration of BA can increase the number of shoots. The increased concentration of BA from 0.5 mg/l be 1-3 mg/l increased the number of propagules, but the number of propagules will decrease in the concentration of BA more 3.5 or 4 mg/l. In addition to BA concentration 0.5, 1 and 1.5 mg/l MS media into producing shoot buds appear faster time high, highest propagules and root amount more on banana propagules Cavendish, but the number of shoots is fewer. The best of BA concentrations to induce propagules plant bananas Cavendish is 3.0 mg/l.